Symmetric Cryptography for Confidential Communications: Implemented by Enhancing the Caesar Cipher - Maihankali, Munura; Chinwe Eze, Esther (International Journal of Computing and Engineering, 2021)
Purpose: This paper identifies and rectifies the key lapses associated with the existing Caesar cryptographic algorithm and further implements the proposed solution, analyses and demonstrates the validity of the improvements effected. The achieved model was implemented as a software solution and duly demonstrated to be a good choice of encryption algorithm in modern-day cryptography. Methodology: The methodology adopted in this study is typically the waterfall model, further incorporating the Object-Oriented Design and Analysis to facilitate the deployment of a cross-platform friendly software implementation of the model solution developed. Computational analysis of the blueprint technique employed to rectify the lapses associated with the existing Caesar cipher e.g., Diffie Helman Technique is elucidated with a more comprehensive description of the architectural design and functionality of the model accessible via: https://github.com/Maihanks/EnhancedCaeserCIpher . A blend of secondary and primary data was used for experimentation and random text data was used to test the modelled solution primarily to validate its feasibility in real-time. Results: The result obtained is a software implementation of the Enhanced Caesar Cipher developed and demonstrated in real-time to be feasible, functional, and cross-platform friendly accessible via: https://github.com/Maihanks/EnhancedCaeserCIpher. It was experimented and demonstrated to have rectified the key lapses associated with the conventional Caesar Cipher analysed and discussed in this paper. Unique contribution to theory, policy, and practice: The result arrived at by the end of the research include: (a) an improved and better version of the Caesar cipher dully implemented, rectifying the conventional Caesar cipher's lapses as described in detail in this paper (b) An automated version of the Caesar Cipher deployed as a software solution (c) A higher complexity for the ameliorated Caesar Cipher with a complexity of O(n2) was achieved which is far better than the conventional Caesar cipher's complexity of O(n). Keywords: Algorithm, Caesar Cipher, Complexity, Cryptography, Symmetric.